(untitled) (Orfeu, 2023)
This article proposes a transdisciplinary dialogue between music, originary musicality, music education and autism. This interlocution will weave a network of ideas, based on research and on our pedagogical experience, seeking to integrate in this weft the concepts of musical development and sociocommunicative development. The goal of this multi-voice counterpoint is to discuss the possible reasons why music, through music education, can open unique windows of communication with the autistic individual. Understanding music as a result of human beings’ original (or innate) musicality, just like the words, we will bring arguments to show that the musical experience systematized by music education brings out, stirs up and provokes this original musicality, allowing the musical development and the organization of the social communication processes, generally compromised in autistic individuals.